(untitled) (Revista de Ingeniería Industrial y Mecánica, 2018)
La problemática que rige de manera integral el sistema de educación superior (SES) genera inquietud con respecto a su calidad, excelencia académica y pertinencia. El análisis de decisión multicriterio es una herramienta que ofrece un marco de decisión cuyo objetivo es elegir entre alternativas basadas en múltiples criterios y saber cuál es el óptimo. El objetivo de este trabajo es evaluar el impacto producido por variables cualitativas y cuantitativas sobre la calidad educativa del SES, para proponer un plan estratégico de gestión integrada. La metodología Multi-Attribute Utility se utilizó con la herramienta de Analytic Hierarchy Process (AHP) y además con la herramienta Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS), ambas herramientas son instrumentos de apoyo en la toma de decisiones. Abstract: The problems that govern the higher education system (HES) in an integral manner generate concern with respect to its quality, academic excellence and pertinence. Multicriteria decision analysis is a tool that offers a decision framework whose objective is to choose between alternatives based on multiple criteria and to know which is the optimal one. The objective of this work is to evaluate the impact produced by qualitative and quantitative variables on the educational quality of the HES, in order to propose an integrated management strategic plan. The Multi-Attribute Utility methodology was used with the Analytic Hierarchy Process (AHP) tool and also with the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) tool, both of which are decision support tools. Keywords: Self-Assessment Model; AHP; TOPSIS; Higher Education System, Multicriteria Decision Models.